2015
DOI: 10.1002/met.1520
|View full text |Cite
|
Sign up to set email alerts
|

Lightning fatalities over India: 1979–2011

Abstract: Information on fatalities in India as a result of lightning flashes has been extracted from a database on disastrous weather events of the India Meteorological Department (IMD). Records dating from 1979 to 2011 indicate that about 5259 persons have been killed by lightning strikes in India. The maximum number of lightning fatalities was observed in the states of Maharashtra (29%), West Bengal (12%) and Uttar Pradesh (9%). The spatial variation shows that lightning fatalities are higher over west central India.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 92 publications
(46 citation statements)
references
References 38 publications
7
39
0
Order By: Relevance
“…Many hazardous phenomena occur with thunderstorms, such as strong gusts, lashing rain, hail and even tornadoes (Puranik and Karekar, 2004) and lightning flashes (Manohar et al, 2008;Nath et al, 2009;Kumar and Kamra, 2012a, b). These severe weather events cause extensive structural damages, destruction of crops, uprooting of trees and casualties (Singh and Singh, 2015;. Bhardwaj et al (2017) observed that about 80% of the total reported thunderstorm casualties in India occur during the pre-monsoon season.…”
Section: Introductionmentioning
confidence: 99%
“…Many hazardous phenomena occur with thunderstorms, such as strong gusts, lashing rain, hail and even tornadoes (Puranik and Karekar, 2004) and lightning flashes (Manohar et al, 2008;Nath et al, 2009;Kumar and Kamra, 2012a, b). These severe weather events cause extensive structural damages, destruction of crops, uprooting of trees and casualties (Singh and Singh, 2015;. Bhardwaj et al (2017) observed that about 80% of the total reported thunderstorm casualties in India occur during the pre-monsoon season.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the publication is unique and the only kind of dataset of its type and thus must be used for this type of analysis. Accordingly, this database has been used earlier for comprehensive studies on extreme weather events (De et al , ), floods (Singh & Kumar, ) and lightning (Singh & Singh, ) in the Indian region.…”
Section: Database and Methodologymentioning
confidence: 99%
“…Among these, Maharashtra ranks 1, West Bengal 2, Uttar Pradesh 3, Kerala 4, and Karnataka 5 (Singh and Singh, 2015). The population densities in Maharashtra, West Bengal, Uttar Pradesh, Kerala, and Karnataka are 365, 1029, 828, 859, and 319 per sq km.…”
Section: Increasing Evaporationmentioning
confidence: 99%
“…As the sun heats up the ground in the warm season, the (Singh and Singh, 2015). rapidly increasing environmental lapse rate (5 K/km) surpasses the dry adiabatic cooling rate (9.8 K/km) in a shallow layer that becomes turbulent.…”
Section: Cumulonimbus Cloud Formationmentioning
confidence: 99%
See 1 more Smart Citation